Write this in y=ax^2+b form:

y=(x-5)^2 - 2

Answers

Answer 1
Answer: Expand (x - 5)^2

(x - 5)^2 = (x - 5)(x - 5)

Multiply all the terms in the first parenthesis to all the terms in the 2nd:

x * x = x^2
x * -5 = -5x
-5 * x = -5x
-5 * -5 = 25

So we have:

x^2 - 5x - 5x + 25

Combine like terms:

x^2 - 10x + 25

Plug it back in:

y = (x - 5)^2 - 2

y = x^2 - 10x + 25 - 2

Combine like terms:

y = x^2 - 10x + 23
Answer 2
Answer: y=(x-5)^2-2\ny=x^2-10x+25-2\ny=x^2-10x+23

Related Questions

The bull's-eye on a target has a diameter of 3 inches. The whole target has a diameter of 15 inches. What part of the whole target is the bull's-eye? Explain
Negative four ninths minus two fifteenths'
Is 16.45 equal to 16.454
A theater technician charges a $200 flat fee and 5% of all profits from ticket sales per show. If the technician made $400.00 on a show, how much total profit was there from ticket sales
What is the GCF of 32 and 56? A.4B.8C.16D.32

Proofs!! can someone PLEASE HELP

Answers

Answer:

nope sorry

Step-by-step explanation:

idk

the peripherals are the same with the numerators acting the quotient

What is 9/4 as a mixed number

Answers

Okay so the formula is

1. Divide the numerator by the denominator.
2. Write down the whole number answer.
3. Then write down any remainder above the denominator.


so your answer is 2 1/4
No, more of an improper fraction

Please help me guys
thank you

Answers

3. 4/5 = 0.8

4. 9/25 = 0.36

5. 1/10 =0.10

6. 7/25 = 0.28

7. 0.45

Hope I helped! (Pick my answer as brainliest!)

Multiply: ( sqrt 2x^3 + sqrt12x) (2*sqrt 10x^5 + sqrt 6x^2)

Answers

Answer:

c is the answer

Step-by-step explanation:

i just did it

Answer:

C

Step-by-step explanatI AM THE EDGENUTITTY GOD

Together, Sarah's two cats have the same mass as her dog, 11 kg. The mass of one cat is1500 g greater than the mass of the other. What are the masses of the two cats?

Answers

First, lets do all calculations in kg. 1kg=1000 grams
Lets set 1 cat's mass as x.
Lets set the other cat's mass as y.
1) x+y=11
2) y=x+1.5   

Lets plug eq 2 into eq 1.
x+x+1.5=11
2x+1.5=11
2x=9.5
x=4.75 kg

If one cat weighs 4.75 kg, then the other must weigh 6.25 kg.




so cat1=x
cat2=y
x+y=11kg
11kg=11000g
x=y+1500
subsitute
y+1500+y=11000
subtract 1500
2y=9500
divide by 2
y=4750
subsitue
x=4750+1500
x=6250

one cat weighs 6250g and the other weighs 4750g

Cassidy said that the capacity is the same as the amount do you agree explain why or why not

Answers

I agree in some ways. If I'm doing this wrong I'm sry I'm just trying to understand.
Yes i think im beacause they are both the same